2002
DOI: 10.4141/p01-043
|View full text |Cite
|
Sign up to set email alerts
|

Mixture performance of phenotypically contrasting barley cultivars

Abstract: Essah, S. Y. C. and Stoskopf, N. C. 2002. Mixture performance of phenotypically contrasting barley cultivars. Can. J. Plant Sci. 82: 1-6. There is lack of information on the yield and yield component performance of same-row and alternate-row mixtures (SRM and ARM) of widely contrasting barley (Hordeum vulgare L.) phenotypes. Therefore, four phenotypically contrasting spring barley cultivars, each selected to represent a unique combination of spike type (two-row or six-row), height (short or tall) and days to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…light regimes in the altered canopies), very little is known about trait plasticity in cultivar mixtures and the extent to which this affects plant growth and development, and in turn cultivar interaction and mixture performance. Essah and Stoskopf (2002) studied mixture performance of barley cultivars with different plant heights. They found a yield advantage compared with pure stands, but not in all combinations.…”
Section: Introductionmentioning
confidence: 99%
“…light regimes in the altered canopies), very little is known about trait plasticity in cultivar mixtures and the extent to which this affects plant growth and development, and in turn cultivar interaction and mixture performance. Essah and Stoskopf (2002) studied mixture performance of barley cultivars with different plant heights. They found a yield advantage compared with pure stands, but not in all combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Juskiw et al (2001) also reported that barley cultivar mixtures had no yield advantage over growing a highly productive mono-cultivar crop. Nevertheless, Essah and Stoskopf (2002) found that mixtures of phenotypically different barley cultivars can produce yield advantages over mono-cultivar crops. Although we attempted to maximize diversity in our experiment, barley cultivars were still randomly chosen and were not purposely selected for contrasting (or similar) traits.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies have shown that barley (Hordeum vulgare L.) grown in mixtures of different cultivars can produce yield advantages over barley grown in monocultures (e.g., Essah and Stoskopf 2002); however, many of the benefits derived from cereal varietal mixtures can be attributed to improved pathogen and pest control (Finckh et al 2000;Cox et al 2004).…”
mentioning
confidence: 99%
“…Using non-elite spring germplasm, such as doubled-haploid lines from a mapping population segregating for two dwarfing genes grown in mixtures, yield enhancement of even two-component mixtures of lines differing in dwarfing genes was 6.6% and for three-components was 9.9% (Newton et al 2004). The strategy of complementing cultivars with contrasting traits was demonstrated using Canadian barley cultivars differing in height and maturity date, illustrating not only the potential for yield enhancement with appropriate combinations, but also some which can lead to negative interactions (Essah and Stoskopf 2002). The resulting canopy structure will affect not only resource utilisation and competition between components and with weeds, but also the environment for infection and transmission of pathogens.…”
Section: Trials and On-farm Usementioning
confidence: 99%